Using hydrogels in microscopy: A tutorial. (May 2016) - Flood, Peter; Page, Henry; Reynaud, Emmanuel G.
Highlights: Use of hydrogel for microscopy sample prep has increased dramatically in recent years. The good optical qualities of hydrogels can be improved using optimized protocols. However, complex physical, chemical and biological properties are often overlooked. These properties can have unexpected consequences on sample development and function. More studies carefully analysing or comparing hydrogels in microscopy are needed. Abstract: Sample preparation for microscopy is a crucial step to ensure the best experimental outcome. It often requires the use of specific mounting media that have to be tailored to not just the sample but the chosen microscopy technique. The media must not damage the sample or impair the optical path, and may also have to support the correct physiological function/development of the sample. For decades, researchers have used embedding media such as hydrogels to maintain samples in place. Their ease of use and transparency has promoted them as mainstream mounting media. However, they are not as straightforward to implement as assumed. They can contain contaminants, generate forces on the sample, have complex diffusion and structural properties that are influenced by multiple factors and are generally not designed for microscopy in mind. This short review will discuss the advantages and disadvantages of using hydrogels for microscopy sample preparation and highlight some of the less obvious problems associated with the area.